Pericruciate fat pad (PCFP) - A scoping systematic review of anatomy, histology, imaging, and clinical importance - Michał Kanak; Marcin Mostowy; Marcin Domżalski; Jędrzej Lesman (Elsevier, 2021)
Goals: Periarticular fat pads of the human knee are relatively well studied structures, but the majority of the reviewed articles focus on fat pads of the anterior part of the knee. Therefore, the goal of this scoping systematic review is to summarize and disseminate current knowledge about the only fat pad in the posterior part of the knee - the pericruciate fat pad (PCFP). Methods: In November 2020 two independent researchers, in order to gather the maximally broad set of articles pertaining to the studied topic, searched the following databases: PubMed, Embase, Karger, Scopus, using terms: pericruciate fat pad, PCL fat pad, posterior cruciate ligament fat pad. The article inclusion criteria was that it contained any scientific or clinical data about the PCFP, regardless of the type of article (original study, case report, review), and the year of its publication. Article exclusion criteria were that the study was not related to the PCFP and the article was written in any other language than English. In order to write each section of this review the included studies were then sorted into subtopics related to the PCFP. Main findings: During the initial search of medical databases only eight articles mentioning the PCFP were identified, and only four directly focused on the PCFP. PCFP is located in the intercondylar fossa, filling the space between cruciates near their femoral attachment sites, surrounding the posterior cruciate ligament (PCL) and directly contacting the posterior capsule of the knee joint. The PCFP is composed of fatty tissue, covered by a thin synovial layer. It can be visualized on a magnetic resonance imaging (MRI) and during arthroscopy. Injuries of the PCFP may occur, resulting in nonspecific posterior knee pain. It has been proposed that alterations of the PCFP signal in MRI were a secondary sign of acute anterior cruciate ligament (ACL) injury, and an early indicator of osteoarthritis of the knee joint. While functions of the PCFP are not yet well studied, the PCFP is hypothesized to be a container of reparative stem cells. In agreement with this hypothesis, "the PCL fat pad transfer technique" was described as a promising treatment to enhance synovialization and revascularization of the ACL, after its repair or reconstruction. Conclusions: Anatomy and imaging of PCFP is relatively well studied, however, we still need additional studies concerning its histology, functions, injuries, and a role in osteoarthritis. While there are theoretical promising benefits of using PCFP in ACL repair or reconstruction, high level-of-evidence research is needed to formulate any stronger opinions on the topic.